Plastisch-chirurgische Rekonstruktion bei ausgedehnten Beckenbodendefekten nach onkologischer Chirurgie - Horch, Raymund E.; Arkudas, Andreas; Ludolph, Ingo; Cai, Aijia; Mulica, Markus (Coloproctology, 2020)
Due to the increasing further development of oncological surgical procedures, in particular extralevatory rectal extirpation in combination with neoadjuvant radiation of the pelvis, the risk of local recurrence of rectal cancer (LRRC) could be reduced to 5–10%. Curative treatment of LRRC necessitates a complete resection with microscopically tumor-free borders (R0); however, the oncologically meaningful radical surgery frequently leads to substantial structural and functional pelvic floor and perineal defects. The resulting mostly irradiated wound cavity after abdominoperineal extirpation (APE) or pelvic exenteration has a high risk of wound healing disorders after primary closure. For primary and also recurrent rectal and anal cancer it was shown that interdisciplinary one-stage reconstructive plastic surgery of the pelvic floor and the perineum and also the vagina, e.g. with a transpelvic vertical rectus abdominis myocutaneous (VRAM) flap, can improve the quality of life and reduce hospitalization times. Even in the long-term course, protracted secondary wound healing disorders can be minimized or avoided using this method.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Interdisciplinary surgery; Pelvic exenteration; Pelvic floor reconstruction; Rectal cancer; VRAM-flap